Comparative subcutaneous and submuscular implantation of an electroencephalography device for long term electroencephalographic monitoring in dogs - Rogers, Casey B.; Meller, Sebastian; Meyerhoff, Nina; Volk, Holger A. (Frontiers in Veterinary Science, 2024)
Background: Implantable EEG recording devices have been used for ultra-long-term epilepsy monitoring both in clinical and home settings in people. Objective and accurate seizure detection and recording at home could be of great benefit in diagnosis, management and research in canine idiopathic epilepsy (IE). Continuous EEG monitoring would allow accurate detection of seizure patterns, seizure cycles, and seizure frequency. An EEG acquisition system usable in an "out of clinic" setting could improve owner and veterinary compliance for EEG diagnostics and seizure management.Objectives: Whether a subcutaneous ultra-long term EEG monitoring device designed for humans could be implanted in dogs.Cadaver study with 8 medium to large breed dogs.Methods: Comparatively using a subcutaneous and submuscular approach to implant the UNEEG SubQ-Implant in each dog. Positioning was controlled via CT post implantation and cranial measurements were taken.In four of the eight dogs a submuscular implantation without any complications was possible. Complications were close contact to the optic nerve in the first approaches, before the implantation angle was changed and in the smallest dog contact of the implant with the orbital fat body. Cranial measurements of less than 95 mm length proved to be too small for Continuous EEG device implantation in dogs reliable implantation via this approach. The subcutaneous approach showed severe limitations and the implant was prone to dislocation.The UNEEQ SubQ-Implant can be implanted in dogs, via submuscular approach. CT imaging and cranial measurements should be taken prior to implantation.